2015
DOI: 10.1007/s10549-015-3652-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a self-management program on antiemetic-induced constipation during chemotherapy among breast cancer patients: a randomized controlled clinical trial

Abstract: Research on patient-reported outcomes indicates that constipation is a common adverse effect of chemotherapy, and the use of 5-hydroxytryptamine (serotonin; 5HT3) receptor antagonists aggravates this condition. As cancer patients take multiple drugs as a part of their clinical management, a non-pharmacological self-management (SM) of constipation would be recommended. We aimed to evaluate the effectiveness of a SM program on antiemetic-induced constipation in cancer patients. Thirty patients with breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 30 publications
(36 reference statements)
1
44
0
9
Order By: Relevance
“…The review of the literature made it possible to conclude that abdominal massage is a form of therapy which is successfully applied in preventing constipation in elderly individuals as well as in patients with multiple sclerosis, Parkinson's disease and spinal cord injuries. The latest research in this field indicated its effectiveness in treating chemotherapy-induced constipation in patients with breast cancer [33]. Moreover, attempts were made at implementing abdominal massage as a method of preventing ventilator-associated pneumonia in enterally-fed patients of intensive care unit [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The review of the literature made it possible to conclude that abdominal massage is a form of therapy which is successfully applied in preventing constipation in elderly individuals as well as in patients with multiple sclerosis, Parkinson's disease and spinal cord injuries. The latest research in this field indicated its effectiveness in treating chemotherapy-induced constipation in patients with breast cancer [33]. Moreover, attempts were made at implementing abdominal massage as a method of preventing ventilator-associated pneumonia in enterally-fed patients of intensive care unit [34].…”
Section: Discussionmentioning
confidence: 99%
“…Różna jest także częstotliwość i czas trwania poszczególnych zabiegów, np. : 1 min/10x dzień -pacjenci poddani chemioterapii w przebiegu leczenia nowotworu piersi [33], 10 min/1x dzień -osoby z chorobą Parkinsona [37], 15 min/2x dzień -pacjenci mechanicznie wentylowani [34]. Trudno jest jednoznacznie stwierdzić, jak długo należałoby aplikować masaż u pensjonariuszy hospicjum, aby uzyskać pożądane rezultaty.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…El masaje comprende diversas técnicas por las cuales un terapeuta mueve, presiona, frota o estira músculos y otros tejidos conectivos en la paciente a un ritmo regular, con varios niveles de presión. 50 Implica una exposición pasiva de la paciente hacia los estímulos que el terapeuta aplica sobre ella y menor actividad física en comparación con el ejercicio, aunque puede haber también una auto aplicación. 51 No es recomendable en pacientes con linfedemas severos o deshidratación.…”
Section: Masajeunclassified